SOST/Sclerostin Improves Posttraumatic Osteoarthritis and Inhibits MMP2/3 Expression After Injury. (2nd April 2018) - Chang, Jiun C; Christiansen, Blaine A; Murugesh, Deepa K; Sebastian, Aimy; Hum, Nicholas R; Collette, Nicole M; Hatsell, Sarah; Economides, Aris N; Blanchette, Craig D; Loots, Gabriela G
ABSTRACT: Patients with anterior cruciate ligament (ACL) rupture are two times as likely to develop posttraumatic osteoarthritis (PTOA). Annually, there are ∼900, 000 knee injuries in the United States, which account for ∼12% of all osteoarthritis (OA) cases. PTOA leads to reduced physical activity, deconditioning of the musculoskeletal system, and in severe cases requires joint replacement to restore function. Therefore, treatments that would prevent cartilage degradation post‐injury would provide attractive alternatives to surgery. Sclerostin (Sost), a Wnt antagonist and a potent negative regulator of bone formation, has recently been implicated in regulating chondrocyte function in OA. To determine whether elevated levels of Sost play a protective role in PTOA, we examined the progression of OA using a noninvasive tibial compression overload model in SOST transgenic ( SOST TG ) and knockout ( Sost ‐/‐ ) mice. Here we report that SOST TG mice develop moderate OA and display significantly less advanced PTOA phenotype at 16 weeks post‐injury compared with wild‐type ( WT ) controls and Sost ‐/‐ . In addition, SOST TG built ∼50% and ∼65% less osteophyte volume than WT and Sost ‐/‐, respectively. Quantification of metalloproteinase (MMP) activity showed that SOST TG had ∼2‐fold less MMP activation than WT or Sost ‐/‐, and this was supported by a significant reduction in MMP2/3 protein levels, suggesting that elevated levels of SOST inhibit the activity of proteolytic enzymes known to degrade articular cartilage matrix. Furthermore, intra‐articular administration of recombinant Sost protein, immediately post‐injury, also significantly decreased MMP activity levels relative to PBS‐treated controls, and Sost activation in response to injury was TNFα and NF‐κB dependent. These results provide in vivo evidence that sclerostin functions as a protective molecule immediately after joint injury to prevent cartilage degradation. © 2018 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals Inc.